Snapshot of the prescribing practice for the clopidogrel and esomeprazole coprescription and cost evaluation of the application guidelines. Issue 3 (21st April 2016) - Vernaz, Nathalie; Rollason, Victoria; Adlere, Liene; Combescure, Christophe; Poncet, Antoine; Bonnabry, Pascal; Desmeules, Jules
Abstract: The antiplatelet clopidogrel and the proton pump inhibitor esomeprazole demonstrate a pharmacokinetic interaction through CYP2C19 that could translate into clinical inefficacy of clopidogrel. No medical consensus as to their coprescription has been reached, and different guidelines are available. We evaluated the prescribing practices at the Geneva University Hospitals (HUG) by measuring whether the coprescription was staggered as suggested by experts. We estimated the financial impact of different implementation guidelines. We used the HUG electronic patient records to follow the physicians' prescriptions and the administration by nurses from January 2013 to April 2014. We performed a time series analysis to assess 15 years of proton pump inhibitors (PPIs) and antiplatelet drug use. "Extra costs" were calculated assuming that clopidogrel or esomeprazole would replace prasugrel or ticagrelor and pantoprazole or ranitidine, respectively. Only 10.8% of the patient medical orders for the clopidogrel and esomeprazole coprescription specified to stagger the administration, 12.6% specified a concomitant coprescription, and 76.6% had no clear information. A high rate of 49.6% of the nurses staggered the clopidogrel and esomeprazole coprescription when no clear information was given. We found a statistically significant decrease in clopidogrel use after the publication of the OCLA (Omeprazole–CLopidogrel–Aspirin) study and a significant increase in the trend of esomeprazole. Alternative treatments to avoid this interaction are cost ineffective or offer therapeutic options of lesser quality. We observed a high rate of 56.2% of the clopidogrel and esomeprazole coprescription in our hospital and can therefore not ignore the PK/PD interaction. The most common prescription practice was to not specify the time frame of administration, which was translated by nurses in 49.6% of the cases to a scheduled staggered coprescription of clopidogrel and esomeprazole. As long as no consensus has been reached, the medical orders time frame information should be mandatory to allow a clear and harmonious staggering strategy.